Correlation coefficients and path analysis of quantitative characters in full-sib progenies of Populus deltoides Bartr. - Singh, N.B.; Singh, Kadam; Choudhary, Punit (The Indian Journal of Genetics and Plant Breeding, 2016)
Correlation and path analysis for direct as well as indirect effects for different quantitative characters responsible for contributing to volume and yield attributes were done in full-sib progenies of selected clones of eastern cotton wood (Populus deltoides Bartr) raised through line x tester scheme. Values of genotypic correlation coefficients were higher than values of phenotypic correlations coefficients and almost similar in direction for most of the characters. The highest significant positive correlation was found between collar diameter and plant height (0.940). Additionally, collar diameter showed significant and positive correlation with plant height at first branch, root length, internodal length, leaf number, leaf area and shoot bark thickness. Of 13 characters, nine characters showed positive direct effect on collar diameter.The largest negative direct effect was contributed by leaf emergence period (– 0.142) followed by leaf number (–0.062), number of branches (–0.054) and branch angle (–0.052). Direct effect of plant height was found highest on collar diameter suggesting its clear direct control over yield attributes in eastern cottonwood.